A Blue Light-Inducible CRISPR-Cas9 System for Inhibiting Progression of Melanoma Cells - Wu, Xia; Huang, Haiyan; Yu, Bo; Zhang, Jianzhong (Frontiers in Molecular Biosciences, 2020)
Melanoma is an aggressive skin tumor that shows a high mortality rate and level of metastasis. BRAF gene mutation (BRAF V600E) is directly related to the occurrence of melanoma. In this study, a light-inducible gene expression system was designed to control the Cas9 transcription, which could then cleave the BRAF V600E. To prove the potential utility of this system in melanoma, the physiological function of melanoma cells was tested. It illustrated that the light-induced CRISPR-Cas9 system could inhibit the progression of G361 and A375 cells. Thus, this system may provide a novel therapeutic strategy of melanoma intervention.